Islamic Religious Education Learning Model in the 21st Century: Systematic Literature Review - Arif, Muhamad; Aziz, Mohd Kasturi Nor Abd (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2023)
Choosing a suitable learning model in Islamic religious education is important in achieving educational goals in the 21st Century. Thus, researchers emphasize two aspects in this study. Firstly, what are the Islamic religious education learning models widely used in the teaching and learning process in the 21st Century? Secondly, what is the urgency of using Islamic Religious Education Learning Models in the 21st Century? A systematic literature review (SLR) was conducted to achieve these objectives, consisting of the selection and PRISMA methodology, which involves systematic planning, identification, feasibility testing, and meta-analysis, including applicable theories of articles from the Crossref and Scopus databases that addressed specific topics (Islamic religious education, Islamic religious education learning, and Islamic religious education learning model). The findings of the analysis indicate that there are nine prevalent learning models utilized by teachers in Islamic religious education: blended learning (BL), problem-based learning (PBL), experiential learning (EL), discovery learning (DL), contextual teaching and learning (CTL), cooperative learning (CL), reflective learning, and electronic learning. This research shows that educators in Islamic religious education can explore and choose learning models appropriate to the teaching material. For example, regarding material on the history of Islamic civilization, teachers can use the discovery learning (DL) method to ensure the Islamic religious education learning process can run optimally according to students' needs.